2022
DOI: 10.13189/cea.2022.100728
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Various Window Orientation in Daylighting Performance in Hot-Humid Climate of Subang, Malaysia

Abstract: This paper discusses the effect of window orientation on the quality of daylight in order to obtain optimum visual comfort in a lecture room in Subang-Kuala Lumpur Malaysia. Visual comfort in buildings is a vital factor to be taken into consideration and has become a priority. Research work is required in order to recognize the limitations, prospects, and challenges of orientation based on working times for daylighting strategy. The lecture room is associated with outdoor and indoor parameters including geogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The evidence that exposure to daylight and views are essential to human life is widely documented for decades (Heschong, 2021;Ludlow, 1976), especially how it impacts human systems such as the visual (Boyce, Hunter, & Howlett, 2003) production of Vitamin D and circadian regulation (Crowley, Cain, Burns, Acebo, & Carskadon, 2015;Mirrahimi, Ibrahim, & Surat, 2013). Currently, daylighting is recognized as one of the most influential factors in creating a positive learning environment, creating optimal conditions for the development of tasks, facilitating learning, and improving performance (Aumann, Heschong, Wright, & Peet, 2004;Rahman & Tuhin, 2019;Susan & Prihatmanti, 2017;Tanner, 2009).…”
Section: The Importance Of Daylight In Classroomsmentioning
confidence: 99%
“…The evidence that exposure to daylight and views are essential to human life is widely documented for decades (Heschong, 2021;Ludlow, 1976), especially how it impacts human systems such as the visual (Boyce, Hunter, & Howlett, 2003) production of Vitamin D and circadian regulation (Crowley, Cain, Burns, Acebo, & Carskadon, 2015;Mirrahimi, Ibrahim, & Surat, 2013). Currently, daylighting is recognized as one of the most influential factors in creating a positive learning environment, creating optimal conditions for the development of tasks, facilitating learning, and improving performance (Aumann, Heschong, Wright, & Peet, 2004;Rahman & Tuhin, 2019;Susan & Prihatmanti, 2017;Tanner, 2009).…”
Section: The Importance Of Daylight In Classroomsmentioning
confidence: 99%
“…Visual conditions depend on parameters such as "brightness distribution, illumination and homogeneity, glare, color of light, color rendering, flicker rate and amount of daylight" (EN 12464-1, 2002). Daylight, which is a source of illumination, is very important on people's health (Edwards & Torcellini, 2002;Hansen, 2006;Košir et al, 2011;Mirrahimi et al, 2013;Acosta & Figueiro, 2015), sustainability of living resources (Dobrin, 1998;Kim & Kim, 2010;Konis, 2013;Korsavi et al, 2016;Al Zaabi et al, 2017), energy saving (Li & Lam, 2001;Bodart & De Herde, 2002;Galasiu & Veitch, 2006;da Fonseca et al, 2013), productivity and success of people (Leather et al, 1998;Fontoynont, Page| 263 2002;Park & Athienitis, 2003;Ruck, 2006;Manav, 2007;Krüger & Dorigo, 2008;Winterbottom & Wilkins, 2009;Erlalelitepe et al, 2011;Samani, 2012;Şansal, 2013;Ahadi et al, 2016;Shishegar & Boubekri, 2016). Therefore, daylight is a necessary and useful strategy for providing visual comfort (Fakhari et al, 2021).…”
Section: Lightingmentioning
confidence: 99%
“…Several recent studies have suggested that environmental factors may also contribute to the onset or aggravation of psychological health [17]. Lighting is one of the most important factors for a positive learning environment [18], and it has an important role in improving the psychological health of students [19]. There is evidence for the significance of lighting for psychological wellbeing, as well as personal health and wellbeing [20].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence for the significance of lighting for psychological wellbeing, as well as personal health and wellbeing [20]. For example, Mirrahimi et al (2013) demonstrated the effects of lighting on the health, psychology, and cognitive abilities of students [19]. In addition, noise has been found to have negative effects on psychological health [21] by causing emotional distress and discomfort [22].…”
Section: Introductionmentioning
confidence: 99%